From Knowledge to Awareness: Educating Orphanage Children in Banjarmasin on Photosynthesis and Environmental Responsibility - Gusti Hadiatus Solehah (Global Education : International Journal of Educational Sciences and Languages, 2025)
This study aims to enhance the environmental awareness of orphanage children in Banjarmasin by educating them on the fundamental concepts of photosynthesis and its crucial role in sustaining life. Through interactive and participatory learning sessions, the program sought not only to impart scientific knowledge but also to foster a sense of environmental responsibility and stewardship. The research employed a qualitative approach, involving observation, interviews, and pre- and post-learning assessments to measure changes in understanding and attitude. Findings indicated a significant improvement in both the children’s comprehension of photosynthesis and their awareness of environmental issues. This suggests that targeted educational interventions can effectively bridge the gap between scientific knowledge and environmental consciousness among young learners in under-resourced communities.